The Distributional Impacts of Indonesia's Financial Crisis on Household Welfare : A 'Rapid Response' Methodology - Friedman, Jed (Washington, DC: World Bank, 2014)
Analyzing the distributional impacts of economic crises is an ever more pressing need. If policymakers are to intervene to help those most adversely affected, they need to identify those who have been hurt most and estimate the magnitude of the harm they have suffered. They must also respond in a timely manner. This article develops a simple methodology for measuring these effects and applies it to analyze the impact of the Indonesian economic crisis on household welfare. Using only pre-crisis household information, it estimates the compensating variation for Indonesian households following the 1997 Asian currency crisis and then explores the results with flexible nonparametric methods. It finds that virtually every household was severely affected, although the urban poor fared the worst. The ability of poor rural households to produce food mitigated the worst consequences of the high inflation. The distributional consequences are the same whether or not households are permitted to substitute toward relatively cheaper goods. Households with young children may have suffered disproportionately large adverse effects.